Morphostructure and Hydrogeochemical Analysis of Geothermal Systems in Karaha Bodas and Talaga Bodas Field, West Java - Ajeng Kania Widiastuti; Dyah Nindita Sahdarani (Jurnal Geologi dan Sumberdaya Mineral, 2022)
The Karaha Bodas and Talaga Bodas are two geothermal fields which are located in Tasikmalaya, West Java. The Karaha Bodas and Talaga Bodas fields have geothermal prospects with the discovery of several surface manifestations in the form of hot springs, fumaroles, and acid lakes. The orientation of the structure that developed in the two fields showed a different orientation. However, no research explains the relationship between the geothermal system in the Karaha Bodas field and the Talaga Bodas field, and the potential of Cipacing and Pamoyanan. The survey location is in Garut and Tasikmalaya, West Java. The investigation method used is qualitative (morphostructure analysis) and quantitative (hydrogeochemical analysis) methods. Data processing using DEM (Digital Elevation Model) for morphostructure analysis, and water chemistry from the Karaha Bodas, Talaga Bodas, and Cipacing fields for hydrogeochemical analysis. The analysis shows that the relationship between the Karaha Bodas and Talaga Bodas geothermal systems is typical a geothermal system, with having two different heat sources, the Talaga Bodas field as an upflow zone, and the Karaha Bodas field with Cipacing and Pamoyanan potentials as an outflow zone.Keywords: Conceptual model, geothermal system, hydrogeochemical, Karaha Bodas, morphostructure, Talaga Bodas.